Covid-19: does it make a difference in ASEAN motor vehicle sales? / Anita Abu Hassan, Najah Mokhtar and Mohd Syazrul Hafizi Husin - Abu Hassan, Anita; Mokhtar, Najah; Husin, Mohd Syazrul Hafizi (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2022)
The COVID-19 virus first appeared in China's Wuhan province in December 2019. The virus spread throughout the world from the Wuhan region. The World Health Organization (WHO) declared the virus a pandemic in March 2020, citing the virus's rapid global infection rate and high mortality rate (Ceylan et al.,2020). The current tally of cumulative cases around the world is 273,900,334 as of December 21, 2021, with recorded total deaths of 5,351,812. With over 50 million cases including over 800,000 deaths, the United States continues to lead all countries in terms of cumulative number of COVID-19 cases. Malaysia, too, recorded a large number of cases, reaching over 2.7 million, with more than 24,000 deaths (World Health Organization, 2021). For the past two years, we have been living in the COVID-19 era. This virus is becoming increasingly virulent and lethal. Not only that it had a significant impact on human health and life, but it also has a substantial impact on most, if not all industries, the economy of a country, and the world in general. Most governments around the world have closed their borders and implemented a lockdown or movement control order to prevent the virus from spreading further.